Patriotism Of Englishman In Shakespeare's King John Drama (1590): A Sociological Approach - Mustamir, Muhammad; , Dr. Phil. Dewi Candraningrum, S.Pd, M,Ed; , Titis Setyabudi S.S., M.Hum (2013)
This Study is about Patriotism. The problem of this study is how patriotism expressed in the King John drama. The object of the study is King John drama by William Shakespeare. It used sociological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the drama text and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusion, based on the analysis it is clear that there is a close relation between this drama and the social reality in England in the middle of the fifteenth century and the beginning of the sixteenth century. Shakespeare wants to criticize the cases of patriotism practices in England in Elizabeth era through King John drama.